The long-term prognostic implications of free triiodothyronine to free thyroxine ratio in patients with obstructive sleep apnea and acute coronary syndrome - Zhou, Yun; He, Qian; Ai, Hui; Zhao, Xuedong; Chen, Xiuhuan; Li, Siyi; Zhang, Zekun; Fan, Jingyao; Gong, Wei; Nie, Shaoping (Frontiers in Endocrinology, 2024)
Abstract Objective: Obstructive sleep apnea (OSA) and thyroid dysfunction frequently overlap clinically and are risk factors for cardiovascular disease. The free triiodothyronine to free thyroxine (FT3/FT4) ratio as a novel biomarker of cardiovascular disease prognosis, but the impact of the FT3/FT4 ratio on the prognosis of OSA in patients with acute coronary syndromes (ACS) remains uncertain. Methods: In this prospective cohort study, 2160 patients with ACS were recruited and underwent portable sleep monitoring at Beijing Anzhen Hospital from June 2015 to January 2020. OSA was diagnosed when apnea-hypopnea index of ≥15 events/h. Patients were further divided into tertiles according to FT3/FT4 ratio. All patients had scheduled follow-up visits at 1, 3, 6, 9 and 12 months after discharge, with subsequent outpatient visits or telephone follow-up visits every 6 months. The primary endpoint was major adverse cardiovascular and cerebrovascular events (MACCE), including cardiovascular death, myocardial infarction (MI), stroke, ischemia-driven revascularization, or hospitalization for unstable angina or heart failure. Results: Among 1,547 euthyroid patients enrolled (mean age, 56.0 ± 10.5 years), 812 patients (52.5%) had OSA. The FT3/FT4 ratio between OSA and non-OSA patients was not significantly different. During 2.8 (1.4, 3.5) years follow up, the risk of MACCE increased with the decreasing FT3/FT4 tertiles in patients with OSA (tertile3 as reference, tertile2: hazard ratio (HR) 1.26, 95% CI: 0.85-1.86, P = 0.255; tertile1: 1.60, 95% CI 1.11-2.32; P = 0.013). After adjustment for confounders, the lowest FT3/FT4 tertile was still independently associated with an increased risk of MACCE (adjusted HR 1.66, 95% CI 1.11-2.50, P = 0.015). Conclusion: Lower FT3/FT4 ratio associated with poor prognosis in patients with ACS and OSA.